GARDEN CULTURE: EFFORTS TO REALIZE A LIVABLE CITY - Rully Besari Budiyanti (Journal of Synergy Landscape, 2021)
Park, as a form of physical culture, is a place for people to experience nature and engage in physical activities while having fun. Therefore, its design must be attractive, easily understood by visitors, and act as a magnet for outdoor activities. Parks play an essential role in facilitating the economy of a city, thereby making it livable. In such conditions, its meaning is in accordance with the setting system formed through a cultural process, which tends to take place continuously over a certain period. Parks produce a culture by interpreting the area located in the habitat to ensure the associated garden is a collection of plants, and various systems, thereby leading to social interaction, cultural manifestations, and nature. The process of interpreting the area as a form of culture can be measured through ideas, concepts, activities, and objects. The park's construction is often followed by the design of a mall equipped with a cooling room, thereby making it a place for social interaction. This study aims to assess Ayodya Park (Taman Ayodya), located in Kebayoran Baru, to determine whether Taman Ayodya has the ability to awaken a gardening culture. Data were collected using survey and observation methods and analyzed using the assessment methods. The results showed that Taman Ayodya had not fully evoked a park culture, rather it is only interpreted as a social interaction park that has provided maximum benefits socially, economically, and environmentally.